WISATA KULINER KOPA (PENDEKATAN DESAIN ARSITEKTUR MODERN TROPIS) - Henry Soleman Raubaba; Anton Topan; Alexander Matius Reyaan (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2018)
Merauke Regency has several recreational places including; Wasur National Park, RI-PNG Border Tourism Area in Sota, Lotus Garden, Kolam Parako, Semesta Commercial Area, PMI Culinary Festival Park. But there are no recreational places that are packaged in an integrated manner which consists of a place to eat, a place to relax, a place to play children. To support the development of Merauke City, a more representative Culinary Center facility needs to be held. The purpose of this study is to plan and design Kopa Culinary Tourism with an attractive visual appearance supported by a site that is accessible to the Modern Tropical architectural design approach. The method used in this research is descriptive research method, carried out by collecting data in the form of interviews with Kolam Parako managers and direct documentation of the object under study. The results of the data obtained are used as a reference to determine the type of space requirements and types of activities. The design of Kopa Culinary Tourism with a land area of ​​5 Ha is divided into 4 parts, namely; (1) Managing Facilities, (2) Culinary Facilities (3) Bathing Facilities (4) Supporting Facilities. Modern tropical architecture approaches are applied including; optimization of natural ventilation and lighting, use of modern materials such as the use of zincalum roof cover, use of GRC partition walls. Kata Kunci: Wisata Kuliner., Kolam Parako Merauke.,Arsitektur Modern Tropis.